2022
DOI: 10.1021/acssensors.2c00154
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Optic Plasmonic Sensors Based on Nanodome Arrays with Nanogaps

Abstract: In this study, a high-performance fiber optic surface plasmon resonance (FO-SPR) sensor using a dome array with nanogaps (DANG) is proposed for label-free real-time detection of biomolecules. A novel and simple method using polymer beads enables high sensitivity by allowing hotspots with nanometer spacing between the Au dome and the surrounding film. The nanodome structure, which comprises a polymer core and a Au shell, induces a localized surface plasmon, expands the sensing area, and extensively enhances the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Copyright 2019 IOP Publishing Ltd. (C) The SEM image and the fabrication of dome array with nanogaps (DANG) for optical fiber-based plasmonic biosensing. (C) Reprinted with permission from ref ( 98 ). Copyright 2022 American Chemical Society.…”
Section: Nanoplasmonic Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2019 IOP Publishing Ltd. (C) The SEM image and the fabrication of dome array with nanogaps (DANG) for optical fiber-based plasmonic biosensing. (C) Reprinted with permission from ref ( 98 ). Copyright 2022 American Chemical Society.…”
Section: Nanoplasmonic Biosensorsmentioning
confidence: 99%
“…The proposed sensor achieved a detection limit of 0.465 μg/mL and a sensitivity of 215 nm/(mg/mL), as depicted in Figure 6 (B). Most recently, Kim et al 98 showed the nanogap dome using the Au for an optical fiber-based plasmonic sensor, illustrated in Figure 6 (C), achieving the detection limit of 38 fg/mL for the antibody–antigen interactions of thyroglobulin.…”
Section: Nanoplasmonic Biosensorsmentioning
confidence: 99%
“…In order to achieve the full potential of SPR-based detection for advanced healthcare, there is a need to miniaturize the bulky instruments required for the coupling of light with propagating SPPs and spectrometers [92]. Also, it is encouraging to achieve advancements in nanofabrication and innovative manufacturing methods, including flexible substrates, 3D printing, and fiber optics for making SPR-based sensors [93][94][95].…”
Section: Plasmonic Thin Film-based Ev Sensingmentioning
confidence: 99%
“…The peak and width values of the SPR absorption spectra are very sensitive to the variation of the sensing layer refractive index. As a result, this configuration can determine the chemical bonds formed between the molecules (for example, biomolecules BioMs) and the sensor (AgNPs). …”
Section: Introductionmentioning
confidence: 99%